An adaptive, color based lane detection of a wearable jogging navigation system for visually impaired on less structured paths - Ramer, Christina; Seßner, Julian; Lichtenegger, Thomas; Landgraf, Maximilian; Franke, Jörg (2016 6th IEEE International Conference on Biomedical Robotics and Biomechatronics (BioRob), 2016)
Based on a previously published version of a first prototypic jogging navigation system for visually impaired and blind people, this paper presents an adaptive lane detection method that extents the use on standard running tracks to general and less structured paths. Additional and supporting developments refer to an active camera stabilization, the improved intuitive vibration feedback and the integrated and embedded mechatronic system setup.

A robot motion planner for 6-DOF industrial robots based on the cell decomposition of the workspace - Ramer, Christina; Reitelshöfer, Sebastian; Franke, Jörg (IEEE ISR 2013, 2013)
This paper describes an autonomous robot motion planner for 6-DOF industrial robots based on the approximate cell decomposition of the workspace. Known obstacles lead to a hierarchical decomposition up to a predefined degree of the start cell which contains the whole robot workspace. A connectivity tree is searched for the shortest path from the start to the goal position for the Tool Center Point (TCP) of the robot. Center points and points between adjacent cells are used as interpolation points for the robot's path. All possible configurations are calculated for these points and checked for absence of collisions and compliance with kinematic constraints. Subsequently paths between possible configurations of interpolation points are checked for feasibility. If points cannot be reached artificial obstacles are constructed and the work space model is updated.
Keywords: cellular manufacturing; collision avoidance; industrial robots; interpolation; mobile robots; robot kinematics; trees (mathematics); 6-DOF industrial robots; TCP; adjacent cells; autonomous collision free path planning; autonomous robot motion planner; connectivity tree; interpolation points; kinematic constraints; path planning problem; tool center point; work space model; workspace cell decomposition; Automation; EMTP; Gold; Mars; Planning; Service robots; 6-DOF industrial robot; cell decomposition method; operational space planner; robot motion planner

Automatisierte Pfadgenerierung und Kollisionsüberwachung für Sechsachs-Industrieroboter durch 3D-kameragestützte Umgebungserfassung - Ramer, Christina; Reitelshöfer, Sebastian; Franke, Jörg (Kongress Automation, 2013)

Combining a collaborative robot and a lightweight Jamming-Gripper to realize an intuitively to use and flexible co-worker - Reitelshöfer, Sebastian; Ramer, Christina; Gräf, Daniel; Matern, Falko; Franke, Jörg (2014 IEEE/SICE International Symposium on System Integration, 2014)
By using collaborative robotic systems, new approaches like programming by demonstration can effectively be realized. As (re)programming of robots thereby gets fast and easy, such systems can facilitate the transition of industrial robots to flexible automation solutions suitable for small companies and small batch sizes. One reason that is preventing the usage of those robots on a broader scale is the fact that for nearly every different work piece a new gripping system has to be designed or at least mechanically adapted. The presented integration of a collaborative robot with a universal Jamming-Gripper broadens the spectrum of parts that can be handled by one robotic system without any mechanical modification.
Keywords: grippers; industrial manipulators; robot programming; collaborative robotic systems; flexible co-worker; gripping system; industrial robots; lightweight jamming-gripper; programming by demonstration; universal jamming-gripper; Educational institutions

Dielectric elastomer actuators - On the way to new actuation-systems driving future assistive, compliant and safe robots and prostheses - Reitelshöfer, Sebastian; Landgraf, Maximilian; Yoo, In Seong; Hörber, Johannes; Ramer, Christina; Ziegler, Christian; Franke, Jörg (5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics, 2014)
For almost 20 years, dielectric elastomer actuators (DEAs) have been the subject of intense research in material science. A large number of publications describe artificial muscles based on DEAs as a promising alternative for an energy efficient, lightweight and flexible actuation architecture. DEAs could improve and extend the capabilities of robotic and prosthetic devices in terms of their dynamical performance and their eligibility for energy autarkic operation. However, up to now DEAs are not available on a large scale with reproducible characteristics nor are they yet usable on a system integration level. In this paper we present recent findings of our ongoing five-year project to qualify DEAs as feasible artificial muscles for usage in compliant robot kinematics and soft prosthetic devices. The focus of this contribution lies on a new automated production process using Aerosol Jet Printing for stacked DEAs with very thin layers for reduced driving voltages and improved mechanical characteristics resulting from the additive manufacturing. Secondly, a new set of lightweight power electronics based on pulse width modulation (PWM) is presented which aims at the improvement of the overall specific power of DEA driven kinematic systems.
Keywords: compliant mechanisms; electroactive polymer actuators; prosthetics; robot kinematics; DEA driven kinematic systems; PWM; actuation systems; additive manufacturing; aerosol jet printing; artificial muscles; assistive robots; automated production process; compliant robot kinematics; dielectric elastomer actuators; lightweight power electronics; pulse width modulation; safe robots; soft prosthetic devices; Biomechatronics; Conferences; Robots

Durchführung von Experimenten und statistische Auswertung - Ramer, Christina; Merhof, Jochen (Handbuch Fügen, Handhaben, Montieren, 2014)
Keywords: Experimente; Simulation

Fusing Low-cost Sensor Data for Localization and Mapping of Automated Guided Vehicle Fleets in Indoor Applications - Ramer, Christina; Seßner, Julian; Scholz, Michael; Zhang, Xu; Franke, Jörg (2015)
This paper describes the joint use of external and on-board low-cost sensors for small to mid-size automated guided vehicles (AGVs) in varying indoor applications. Localization and mapping for navigation purposes of multi-scale vehicle fleets is achieved by combining fixed, one-time calibrated cameras with odometry information and cheap LIDAR (Light detection and ranging) and collision avoidance sensors, which are mounted on the vehicles. Our approach is scalable and applies to different domains, as logistics in production environments or hospital facilities. Experiments show that the proposed system concept, based on low-cost units, reaches sufficient accuracy in real-time and could therefore be a promising solution for the target applications.

Kollisionsfreie Bewegungsgenerierung für ein Industrieroboter-Assistenzsystem auf Basis von 3D-Kameradaten - Ramer, Christina; Franke, Jörg (Internationales Forum Mechatronik 2013, 2013)
Herkömmliche Industrieroboter müssen auf Grund ihres Gefährdungspotentials strikt von Bereichen, in denen Menschen arbeiten, getrennt werden. Die Programmierung ist bei komplexen Umgebungen aufwendig, sodass sich der Einsatz nur bei ausreichend hohen Stückzahlen lohnt. Auf Grund dessen werden Industrieroboter trotz der bekannten Vorteile gegenüber manueller Ausführung - wie Schnelligkeit, Ausdauer und Genauigkeit - in vielen Bereichen nicht eingesetzt, obwohl die Unterstützung von Produktionsmitarbeitern zur Vermeidung körperlich anstrengender und monotoner Aufgaben wünschenswert wäre. Dieser Beitrag stellt einen Ansatz für ein Roboterassistenzsystem vor, bei dem über eine 3D-Kamera basierte Arbeitsraumerfassung sowie manuell definierte Hindernisse ein aktuelles Umgebungsmodell generiert und automatisch eine kollisionsfreie Bahn für einen Sechsachs-Knickarmroboter errechnet wird. Dadurch kann der Einsatz von Robotern bei nicht vorhandenem Fachpersonal zur Umprogrammierung sowie bei kleineren Stückzahlen attraktiver werden. Es ergeben sich auch weitere Anwendungsgebiete für Industrieroboter, beispielsweise zur Unterstützung leistungsgewandelter oder geminderter Personen im Erwerbsleben. Eingangsparameter der automatischen Pfadgenerierung sind die aktuelle Istposition des Roboters und eine kartesische oder achsbasierte Zielposition. Eine hierarchische Zellzerlegung des Roboterarbeitsraums berechnet hierauf kollisionsfreie Zellen sowie mittels eines angepassten A*-Algorithmus den kürzesten Weg benachbarter, freier Zellen von der aktuellen Start- zur vorgegebenen Zielposition für den Werkzeug-arbeitspunkt (TCP, Tool-Center-Point) des Roboters. Es können sowohl synchrone Point-to-Point (PTP) als auch Linearbewegungen berücksichtigt werden. Die Orientierungsänderung zwischen Start- und Zielposition wird an die Wegänderung gekoppelt. Für alle Pfadstrecken zwischen den ermittelten kartesischen Stützpunkten wird in definierten Abständen eine hierarchische Kollisionsprüfung des Roboterarms mit der Umgebung durchgeführt. Hierfür werden bei Verwendung des PTP-Modus zunächst alle gültigen Konfigurationen der Stützpunkte und die sich daraus ergebenden, realisierbaren Kombinationen bestimmt. Falls Linearbewegungen erforderlich sind oder bevorzugt werden sollen, erfolgt zudem die überprüfung der Pfadabschnitte auf singuläre Stellungen, die zu einem Verwerfen der Bahn führen. Falls ein Stützpunkt oder ein Pfadabschnitt keine gültige Konfiguration liefert, wird ein künstliches Hindernis an der TCP-Position eingefügt und auf Basis des aktualisierten Arbeitsraummodells eine erneute Zellzerlegung und TCP-Pfadsuche angestoßen. Um die notwendigen Kollisionsberechnungen zu beschleunigen, werden die Hindernisobjekte sowie der eingesetzte Roboter durch geometrisch einfache Hüllkörper umschlossen und überschneidungen mit dem Roboter hierarchisch geprüft. Neben der automatischen Bewegungsgenerierung wird im weiteren Verlauf dieses Beitrags als Erweiterung des beschriebenen Ansatzes auch die Möglichkeit einer Kollisionsüberwachung während der Roboterbewegung bei einem Einsatz ohne trennende Schutzeinrichtungen vorgestellt, sodass die Gefährdung von Menschen durch ein Anhalten des Roboters vermieden werden kann. Dabei werden auf Basis des aktuellen Arbeitsraummodells und der bekannten Roboteristposition hierarchische Abstandsprüfungen zu dynamischen Objekten und Personen durchgeführt und auf die Einhaltung eines angepassten Mindestsicherheitsabstandes geprüft.
Keywords: Assistenzsystem; Bahnplanung; ToF-Kamera; Arbeitsraumüberwachung; B|Mech

My new colleague has artificial muscles: a DEA based approach for inherently compliant robotic systems - Yoo, In Seong; Landgraf, Maximilian; Ramer, Christina; Reitelshöfer, Sebastian; Ziegler, Christian; Franke, Jörg (Production Engineering, 2014)
Keywords: Artificial muscles; Compliant actuators; Dielectric elastomer actuators; Electroactive polymers; Human–robot collaboration; Safe robotic systems

Roboterassistenz in der Behindertenwerkstatt: Intuitiv bedienbare, sichere und flexible Zusammenarbeit mit Industrierobotern - Leutert, F.; Ramer, Christina; Pirkl, G.; Bahle, G.; Poxrucker, A.; Dresselhaus, M.; Ziegler, Christoph; Schilling, K.; Franke, Jörg; Lukowicz, P. (wt Werkstattstechnik - Online, 2014)
For a successful collaboration between humans and robotic assistants in a shared workspace, users must be enabled to intuitively understand robotic data and work processes, to easily operate the robot while being protected from harm by safety systems. This article introduces an assistance system employed in sheltered workshops that achieves these goals using Augmented Reality, novel input devices, and automatic collision avoidance.
Keywords: B|Mech

Robust Obstacle Mapping for Visually Impaired Jogger on Less Structured Paths - Seßner, Julian; Ramer, Christina; Manert, Moritz; Reitelshöfer, Sebastian; Franke, Jörg (2019 IEEE/SICE International Symposium on System Integration, 2019)
This paper presents robust mapping of obstacles for an assistive system for blind and visually impaired jogger. The missing visual perception is substituted with a 3D stereo camera, capturing color and depth information from the environment. It is integrated into a lightweight backpack together with a single board computer. This paper focusses on the obstacle detection and mapping using the v-disparity method. To enhance the robustness of the mapping algorithm a roll angle detection and compensation is implemented. The algorithms are evaluated in different environments and proved their feasibility. The framerate is sufficient to detect obstacles in tim

Sensor-guided jogging for visually impaired - Ramer, Christina; Ziegler, Christian; Reitelshöfer, Sebastian; Franke, Jörg (5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics, 2014)
This paper introduces an approach for enabling visually impaired and blind people to practice jogging activities by 3D environment perception for course detection and collision avoidance, as well as feedback generation in an intuitive manner. Besides a system concept, first prototypic realizations, that confirm the general feasibility, are presented for this domain, which has not been addressed by research until now.
Keywords: handicapped aids; object detection; optical sensors; 3D environment perception; blind people; collision avoidance; course detection; feedback generation; optical sensors; sensor-guided jogging; visually impaired people; Belts; Cameras; Navigation; Sensors; Standards; Three-dimensional displays; Visualization

(untitled) - Ramer, Christina (Handbuch Fügen, Handhaben, Montieren)
Keywords: Simulation; Vorgehensweise

Work space surveillance of a robot assistance system using a ToF camera - Ramer, Christina; Franke, Jörg (Advanced Materials Research, 2014)
Aufgrund der demographischen Entwicklung in Industrienationen liegt eine wachsende Herausforderung darin, Produktionsmitarbeiter durch eine Reduzierung von Belastungen vor möglichen Gesundheitsschäden zu bewahren und eine längere Erwerbstätigkeit zu ermöglichen. Ebenso ist es erstrebenswert, die Potentiale leistungsgewandelter Personen zu nutzen, wodurch angepasste Hilfsmittel zur Erleichterung des Arbeitsalltags benötigt werden. Um bereits gesundheitlich vorgeschädigte Personen schneller wieder in ihren Beruf einzugliedern, erscheint es zudem denkbar Rehabilitationsmaßnahmen durch geeignete Roboterassistenten zu unterstützen. Diese Ziele werden bei der Entwicklung des vorgestellten Roboterassistenzsystems verfolgt. Um Menschen sicher im Arbeitsraum eines assistierenden Roboters erkennen und verfolgen zu können, werden visuelle Sensortechnologien zur 3D-Raumüberwachung benötigt. Herkömmliche Kamerasysteme, die ein 2D-Intensitätsbild ihrer Umgebung liefern, sind stark anfällig gegenüber Helligkeitsänderungen, was ein sicheres Personentracking kaum möglich macht. Ein neuerer Vertreter der indirekten Licht-Laufzeitmessung (Time-of-Flight, ToF) stellt die PMD (Photonic Mixing Device)-Technologie dar, bei der die Entfernungsinformation in jedem Pixel einer Sensormatrix in Echtzeit bestimmt werden kann. Auf Grund der Vorteile wurde für das Assistenzsystem eine ToF-Kamera ausgewählt. Im Versuchsaufbau wurde die Kamera zunächst zentral über dem überwachungsraum angebracht, um weitestgehend alle Kollisionsobjekte ohne Abschattungen detektieren zu können. Zu Beginn der Arbeitsraumüberwachung werden die vorverarbeiteten 3D-Koordinaten zusammen mit den bereitgestellten Intensitäts- und Amplitudenwerten der ersten Kameraframes zur Generierung eines Referenzbildes herangezogen. Die Detektion von Kollisionsobjekten erfolgt über die Differenzbildung zwischen initialem Hintergrund- und dem aktuellem Kamerabild. Aus den Differenzwerten wird für jedes Pixel die Wahrscheinlichkeit, ein Objekt abzubilden, berechnet und in diskrete Klassifikationsstufen eingeordnet. Sie ergibt sich im Wesentlichen aus der Höhen- und Intensitätsdifferenz des betrachteten Pixels sowie dessen acht Nachbarpixeln. Mittels eines Region-Growing-Algorithmus werden alle Nachbarn von Pixeln einer hohen Klassifikationsstufe, den sogenannten Start- oder Seedpixeln, in einem der Objektwahrscheinlichkeit angepassten Umkreis untersucht und im Falle einer hohen Objektwahrscheinlichkeit zu diesen hinzugezogen. Die Erstellung einzelner Objekte erfolgt aus zusammenhängenden Bereichen mit mindestens vier Bildpunkten. Um erkannte Objekte wiedererkennen zu können, werden diese mit einer Reihe ermittelter Attribute gespeichert. über eine Hochrechnung der aktuellen Position wird zunächst nach bekannten und in einem weiteren Schritt nach neuen Objekten gesucht. Die Wiedererkennung bereits detektierter Kollisionsobjekte erfolgt bei der überschreitung eines in Versuchen ermittelten übereinstimmungswerts, der sich aus mehreren Vergleichs-kriterien zusammensetzt. Eine automatisierte Bahnplanung ermöglicht den Einsatz auch bei veränderten Umgebungsbedingungen des Assistenzsystems, ohne auf geschultes Personal zum Teachen des Roboters zurückgreifen zu müssen. Um die für die zeitkritische Kollisionsvermeidung und die Pfadfindung notwendigen Abstandsberechnungen zu be-schleunigen, werden die detektieren Kollisionsobjekte mittels einfacher Hüllkörper, sogenannter Bounding Volumes, approximiert. Eingesetzt werden orientierte Hüllquader (Oriented Bounding Boxes), Hüllzylinder und kugeln sowie sogenannte -kapseln (Zylinder mit Halbkugelenden). Basierend auf einer sensorischen überwachung des Roboterarbeitsraums in Echtzeit und der dynamischen Anpassung des Umgebungsmodells kann somit die Basis geschaffen werden, um einen kollaborierenden Betrieb zwischen zu unterstützenden Werkern und dem Roboterassistenten zu ermöglichen.
Keywords: Arbeitsraumüberwachung; Roboterassistenzsystem; ToF-Kamera; PMD-Kamera; 3D-Kamera; Objekterkennung; B|Mech